Nitrogen Sources and Rate for Drip Irrigated Polyethylene Mulched Chilli Pepper - Deli, Syekh Zulfadli Arofah; Susila, Anas Dinurrohman; Purwono, Purwono; Suketi, Ketty (Journal of Tropical Crop Science, 2019)
Chilli pepper is the one of most important vegetable crops in Indonesia, and nitrogen is an essential macronutrient ‎to support plant growth. This study was conducted to determine the best source of nitrogen (N) and its optimum rate ‎for drip irrigated polyethylene mulched chilli pepper at. The study site is located at ‎‎ Tajur II ‎Experimental Field of Center for Tropical Horticulture Studies Bogor Agricultural University, West Java, Indonesia, 250 m above the sea level (-6.6364580S, 106.8231460E) from January to August 2018. The experiments were organized in a factorial split-plot with sources of‎ N fertilizer as the main plots (Urea, ‎NPK, and ZA) and rates of N as a sub-plots (0, 115, 230, 345, and 460 kg.ha-‎‎1). The ‎results showed that NPK fertilizer had the best source of N compared to ‎other sources. The maximum yield of 9.01 kg per plot, or equivalent to ‎10.46 t.ha-1, was obtained with N fertilization at 265 to 295 kg.ha-1.‎